Avaliação dos efeitos da radiação micro-ondas na atividade heterogênea e estabilidade química de nanopartículas de magnetita em processos oxidativos avançados - Vieira, Yasmin (2020)
In this research, for the first time, is reported the role of microwave (MW) radiation into the heterogeneous activation of nano–Fe3O4. Since magnetite has been extensively used as catalyst in advanced oxidative processes (AOPs), Rhodamine B (RhB) degradation was set as the model reaction with the aim of observing MW effects altogether. The nano–Fe3O4 were synthesized by co–precipitation method and characterized by several techniques. By using a star type central composite design (CCD) followed by response surface methodology (RSM) and principal component analysis (PCA), the optimal operational parameters for the catalytic reactions were defined as 0.4 g L–1 of nano–Fe3O4, [H2O2]/Mineralization ratio equal to 1 and pH of 2.4. MW power was set at 500 W. In these conditions, nano–Fe3O4 presented remarkable reusability up to seven cycles. RhB degradation pathway was verified by LC–MS/MS and GC–MS/MS. It was determined that •OH were the major ROS generated during the reaction, and an interfacial catalytic mechanism was proposed. Total decolorization was reached in only 7 min, with total TOC removal of 97.55%. The high efficiency obtained reflects the formation of hot spots and nonthermal effects of MW. Therefore, when operational conditions are adequate, nano–Fe3O4 proved to be a remarkably efficient catalyst for AOPs when MW irradiated as also fully heterogeneous and recoverable, with less than 1% of homogeneous contribution to the process.